The Vessel of Inland Waterways System - Shatat, Saleh Raed; Victoria, Ong Argo; Mahammed, Mohammed Abdela (IWTJ : International Water Transport Journal, 2020)
The granting of measuring letters, registration and registration certificates, ship worthiness certificates and ship manning certificates for vessels under GT 7 (<7 GT) were given by the Regent / Mayor as a decentralization task. The granting of measuring letters, registration certificates and registration certificates, ship worthiness certificates, vessel manning certificates, and nationality certificates for ships with sizes ranging from GT 7 and above (> 7 GT) are given by the local Regent / Mayor as assistance tasks. This is still valid until the issuance of the Latest Ministerial Regulation on Certification of River and Lake Ships.